Entrepreneurship Teaching : Design and Activities of 21st Century Learning for Economic Class under Mini-Project (Participatory-Phenomenological Design) - Fahrurrozi, Muh (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to explain the process of teaching entrepreneurship education courses in economics classes under a detailed mini-project. This research used Participatory action research (PAR) under qualitative approach. The sample size was only taken purposefully from one semester's three economics classes. This research used observation sheets in the form of learning activities and interviews.Â  All data collected were analyzed descriptively with the step of reducing, displaying and drawing conclusion. The research results showed the effectiveness of a bidirectional teaching model in entrepreneurship education. This model, which combines theoretical instruction with practical application, significantly enhances student engagement and learning outcomes. The bidirectional approach allows students to relate theoretical concepts to real-world examples, fostering a deeper understanding and active participation. An essential element of this teaching model is the inclusion of mini-projects. These projects enable students to apply theoretical knowledge in practical scenarios, such as developing business plans and analyzing recruitment strategies. The hands-on experience gained through mini-projects not only solidifies students' grasp of the material but also hones their problem-solving and critical-thinking skills. The study's findings underscore the superiority of the bidirectional teaching model over traditional methods. The experimental class, which utilized this approach, showed a 93% success rate in meeting various evaluation criteria, compared to just 30% in the control class. This stark contrast highlights the importance of integrating mini-projects and practical activities into the curriculum to enhance educational outcomes. The bidirectional teaching model, complemented by mini-projects, proves to be a highly effective approach in entrepreneurship education. It not only engages students more deeply but also equips them with practical skills and knowledge that are essential for their future careers.